Proceedings. 1984 IEEE International Conference on Robotics and Automation
DOI: 10.1109/robot.1984.1087225
|View full text |Cite
|
Sign up to set email alerts
|

Feeling by grasping

Abstract: This paper specifies constraints based on the geometry of the grasped object, on geometry of the hand and the kinematics of the constrained object which determine how to grasp an object.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…From the beginning (since the 1980s) of our efforts in Active Perception we realized that vision is limited and has to be complimented by tactile perception. This has been documented by series of papers: Shape from Touch (Bajcsy 1984), Active Touch (Goldberg and Bajcsy 1984), and Feeling by Grasping (Bajcsy et al 1984). Allen (1985) showed that tactile perception is preferred to vision when an agent must discriminate different material properties of hardness, demonstrating this on discriminating the hole on the cup handle vs. the body of the cup.…”
Section: How Does An Agent Control How Sensing Occurs?mentioning
confidence: 95%
“…From the beginning (since the 1980s) of our efforts in Active Perception we realized that vision is limited and has to be complimented by tactile perception. This has been documented by series of papers: Shape from Touch (Bajcsy 1984), Active Touch (Goldberg and Bajcsy 1984), and Feeling by Grasping (Bajcsy et al 1984). Allen (1985) showed that tactile perception is preferred to vision when an agent must discriminate different material properties of hardness, demonstrating this on discriminating the hole on the cup handle vs. the body of the cup.…”
Section: How Does An Agent Control How Sensing Occurs?mentioning
confidence: 95%
“…* (A similar proposal has been made for robotic grasping. 7 ) The benefits of coordination, and the potential disadvantages of uncoordinated movement, suggest that the former will dominate multiple-effector exploration, whatever the processing goal.…”
Section: Independent Vs Coordinated Effectors: Competing Input Channmentioning
confidence: 99%
“…Condition ( 2 ) reflects the fact that nE > nc; when the mobility constraints are dependent (see eq. 51).…”
Section: Theorem 1 a Grasp Is Quasi-statically Determinate If And Onlmentioning
confidence: 99%